A quantitative strategy of ultrasound-assisted digestion combined UPLC-MS/MS for rapid identifying species-specific peptide markers in the application of food gelatin authentication. (July 2021) - Cai, Shuo; Jiang, Mengtong; Zhao, Kexuan; Huang, Xiaozheng; Fei, Fei; Cao, Bei; Cui, Xiaobin; Duan, Jin-ao; Zhao, Ming; Han, Shuying; Liu, Rui
Abstract: Gelatins are important and frequently-used food additives, but the quality control of gelatins is always an intractable problem in routine analysis. In this work, a new strategy for simultaneously rapid identification and quantification of gelatins from various species using ultrasound assisted digestion-UPLC-MS/MS was described. Fourteen peptide markers were used for authenticity of gelatins by the presence or absence of these species-specific peptides. In the meantime, adulteration ratios could be calculated based on the peak area of different species peptide markers. With 10 g/L trypsin and ultrasound application, digestion time could be decreased from >12 h (traditional method) to 5 min, and the determination of animal gelatins could be achieved in 20 min with a single analysis run. Twenty-five commercial gelatin samples were screened, among which two deer-hide gelatin samples were adulterated with 900 g/kg and 265 g/kg cattle-hide gelatin (CHG); two donkey-hide gelatin (ACC) samples were adulterated with 66 g/kg and 381 g/kg horse-hide gelatin; and one ACC sample was adulterated with 786 g/kg CHG. This strategy provides an efficient and sensitive authentication and traceability of gelatin-containing products, and could also be applied to processed meat or protein food. Highlights: Ultrasound assisted digestion-LC-MS/MS was developed for gelatin authentication. Simultaneous identification and quantification were achieved in 20 min. The cost-effective strategy makes processed food authenticable and traceable.